EFEITO DA APLICAÇÃO DE UM ANÁLOGO DE BRASSINOSTERÓIDE SOBRE A MATURAÇÃO DA UVA „NIÁGARA ROSADA‟ - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2011)
The grape is considered the most important fruit in the world economy and its quality is directly related to its point of maturity. The mechanisms that regulate their maturation are still poorly understood despite the great effort to this end. Recently, evidence from genetic studies revealed that brassinosteroids, plant hormones recently discovered, appear to be involved in the maturation of grapes. Thus the aim of this study was to assess the effect of different concentrations of an analogue of brassinosteroid the BIOBRAS-16 (BB-16), on the maturation of 'Niágara Rosada' grapes. Two experiments were conducted, one in 2009/10 and another in the 2010/11 season, in a commercial vineyard in the city of Ponta Grossa - PR. In the first experiment were tested at concentrations of 0, 0.1, 0.5, 5.0 and 50 mg L-1 BB-16 applied to different bunches, at 4 times every 7 days from the stadium of compact clusters . In the second experiment were tested at concentrations of 0, 0.5, 5.0 and 50 mg L-1 BB-16 applied in different berries from the same bunch, at 4 times every 7 days from the stadium in compact clusters . The design was a randomized block design with four replications for the 2009 harvest and 10 repetitions for 2010. BB-16 at a concentration of 5.0 mg L-1 significantly promoted the anticipation of the beginning of pigmentation of the berries in about 5 days for both seasons and provides a larger percentage of light colored berries and smaller berries in stages early maturation, indicating a higher production of anthocyanins. BB-16 also caused the increased diameter, length and weight of berries in season 2010, when the treatments were applied in the same cluster. In relation to soluble solids, the concentration of 5.0 mg L-1 BB-16 caused significant increases in berry in 2009. This same concentration also caused a higher soluble solids / acidity and a possible anticipation of the harvest. Titratable acidity and pH were not affected by BB-16, in both seasons. This study highlights the need for more studies on the effect of BRs, not only when applied over the berries, but also on the leaves. Also, the need to test new concentrations and its interaction with other plant hormones. BB-16 was shown to be an interesting tool for increasing productivity and quality of grapes.
Keywords: videira; véraison; regulador vegetal; BIOBRAS-16; vine; veraison; growth regulator; BIOBRAS-16; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA